Investigating the relationship between volume transport and sea surface height in the Agulhas Current System - Vermeulen, Estee (Department of Oceanography, 2018)
The relationship between the volume transport of the Agulhas Current at 34°S (the position of the Agulhas Current Time-series array) and the gradient of sea surface height across the current was investigated using a regional Hybrid Coordinate Ocean Model. Previous studies have suggested a high correlation between SSH slope and Agulhas Current transport and, based on 3 years of in situ measurements, a transport proxy between along-track satellite data and in situ data was developed. The purpose of this modelling study was to re-create the Agulhas Current transport proxy in a virtual modelling environment, to test the validity of the underlying assumption on which the satellite-altimeter proxy was based. The Agulhas transport proxy assumed nine, constant linear relationships between SSH slope and integrated transport per unit distance over the 22-year transport time-series, based on the 3-year sampling period and a constant vertical stratification. The 34-year regional-hindcast from HYCOM provided the means to test the sensitivity of the transport proxy to vertical changes in the current and the length scale of observations used to build a constant, linear relationship between transport and SSH slope. During the investigation it was found that HYCOM contained exaggerated levels of offshore variability. This resulted in stronger correlations for the inshore linear regression models with a decreasing trend moving offshore. Based on the overall performance of the 34-year transport proxies it was concluded that the proxy was more capable of estimating the net transport of the Agulhas Current across the array instead of only the southwest transport component. Therefore, transport estimates inshore were more accurate than the transport estimates offshore, when the current is in a meandering state, and the poorer performance of the southwest transport proxy, specifically developed to capture the transport during offshore meander events, was less capable of estimating an accurate transport estimate. Results showed that calculating the proxy over longer time periods did not significantly improve the skill of the Agulhas transport proxy, suggesting the 3-years was a sufficient time-period used to develop the transport proxy in HYCOM. This study motivates the need to improve long-term monitoring methods, where the usage of numerical ocean models could help understand the sensitivities and limitations involved in the development of transport proxies in future.